Kindergarten Students Acquire Basic English Literacy Through Letterland: A Case Study - Limbong, Joice Ellen (LPPM Universitas Advent Indonesia, 2018)
This study aims to help kindergarten students to acquire basic literacy in English through the use of Letterland which is believed to be a fun and exciting program which can produce a natural outcome. This study utilizes qualitative and quantitative approach. The research design of this study is case study in order to make intensive analysis on how kindergarten students acquire Basic English literacy through Letterland. The study presents a description on how effective and helpful Letterland is in helping kindergarten students acquire basic literacy. This study can be used to provide local teachers or educators with the ideas in implementing the phonics approach in teaching Basic English literacy. There are number of factors that enable students to acquire the Basic English literacy; however, this study focuses on the application of Letterland. Findings showed that Letterland is useful to help kindergarten students in school K in acquiring Basic English literacy. Students recognized the initial, medial and final sounds. The teachers implemented Letterland with a proper class settings, sufficient teaching aids, and proper teaching-learning process. Keyword Letterland, Basic English Literacy, Kindergarten